Determinan Penyerapan Tenaga Kerja Sektor Industri Manufaktur Besar dan Sedang di Indonesia - Disti Khuzi, Mela; Nelonda, Selli; Dina, Rusy (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Labor absorption reflects the company's capacity to employ labor. The large and medium-scale manufacturing sector has an important role in supporting the Indonesian economy, with the hope of providing added value and absorbing a significant amount of labor. This study aims to evaluate the effect of wage, capital, and output variables on the level of labor absorption in the sector, using panel data from 34 provinces during the period 2017 to 2022 through a fixed effect model approach. The results of the analysis show that wage and output variables have a positive and significant impact, while capital shows a negative and significant effect on labor absorption in the large and medium manufacturing industry sector. This finding suggests that increasing capital risks encouraging automation that reduces the role of labor. Therefore, policies are needed that support labor-intensive sectors so that technological efficiency remains in line with increasing employment opportunities.